Green Marketing Mix: A Model towards Sustainability - Goyal, M; Pahwa, M.S (International Journal of Computer Sciences and Engineering, 2025)
As a result of histrionic increase in global environmental cognizance, the concept of green marketing has emerged as a buzzword over the last decade. In modern businesses, sustainability has become an effective marketing tool and sustainable living brands are growing extraordinarily faster than those of other business. The new green innovations in marketing mix, like eco-friendly products, green logistics, etc. empowers them to access new markets, augment their market shares, and ultimately increase profits. Just as we have 4Ps i.e. product, prices, place and promotion in marketing, we have 4Gs in green marketing too, but they are bolstered by sustainability as vision. The paper highlights current green marketing mix strategies used by businesses to compete in the market and aims to report the findings of review of literature in green marketing domain and propose a green marketing mix model to attain sustainability. This exploratory research paper also discusses consequent implications for marketers in designing their sustainable marketing strategies